2015
DOI: 10.1371/journal.pone.0132367
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Induces Vascular Hyperpermeability by Increasing Blood Flow and Endothelial Barrier Disruption In Vivo

Abstract: Histamine is a mediator of allergic inflammation released mainly from mast cells. Although histamine strongly increases vascular permeability, its precise mechanism under in vivo situation remains unknown. We here attempted to reveal how histamine induces vascular hyperpermeability focusing on the key regulators of vascular permeability, blood flow and endothelial barrier. Degranulation of mast cells by antigen-stimulation or histamine treatment induced vascular hyperpermeability and tissue swelling in mouse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 27 publications
4
131
0
1
Order By: Relevance
“…Phosphorylation of VE-cadherin by tyrosine is a general mechanism involved in weakening of the endothelial cell barrier resulting from cell stimulation. It is likely that histamine and bradykinin, the 2 main mediators involved in angioedema, exert their permeabilizing effect mainly through phosphorylation of VE-cadherin [7,8]. Detection of soluble VE-cadherin in the serum of patients with a form of primary angioedema during an attack reinforces this view [9].…”
Section: Pathophysiologymentioning
confidence: 89%
See 1 more Smart Citation
“…Phosphorylation of VE-cadherin by tyrosine is a general mechanism involved in weakening of the endothelial cell barrier resulting from cell stimulation. It is likely that histamine and bradykinin, the 2 main mediators involved in angioedema, exert their permeabilizing effect mainly through phosphorylation of VE-cadherin [7,8]. Detection of soluble VE-cadherin in the serum of patients with a form of primary angioedema during an attack reinforces this view [9].…”
Section: Pathophysiologymentioning
confidence: 89%
“…The 2 major factors that determine vascular permeability are blood flow and endothelial barrier function [10]. In the case of histamine, a recent study revealed that hyperpermeability is due mainly to the NO-induced increase in blood flow, which in turn is controlled by stimulation by vascular endothelial growth factor [7,11]. According to this finding, rubor and calor are features of histaminergic urticaria and tend to be more evident in histaminergic forms of angioedema than in nonhistaminergic forms.…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, the exact contribution of various segments of the tumour neovasculature to permeability remains poorly understood. In addition to an arsenal of inflammatory mediators such as histamine 106,107 , the interaction of tight junction modulators such as cationic polymers with endothelium can also induce endothelial contraction and tight junction disassembly, leading to vascular leakiness 108 . For tumours, both vascular permeability and blood velocity are complex and kinetically variable from segment to segment 109 .…”
Section: Enhancing Drug Delivery To the Tumourmentioning
confidence: 99%
“…Our results demonstrate that BaP1 is able to disrupt the endothelial barrier in PCV in the in vivo model. This change in the morphology induced by BaP1 in cell-cell junctions is similar to that described after an inflammatory stimulus, and is associated with changes in VE-cadherin localization, internalization or disassembly [4749]. Interestingly, a mechanism of SVMP-induced extravasation, known as haemorrhage per diapedesis , has been described in PCV; in this case erythrocyte extravasation occurs through widened intercellular junctions in venular endothelial cells [11].…”
Section: Discussionmentioning
confidence: 59%